The Political Myth in the Novel “The Land of Nairi” by Ye. Charents - Hovhannisyan, Christine (Bulletin of Yerevan University B: Philology, 2024)
The political layer of Charents’ novel ՛՛The Land of Nair’’ was mainly examined in literary studies in the context of the relationship with the novel’s prototype characters and documentary materials. The center of the studies were the author’s attitude towards the parties of the time, the Russian revolution, and Soviet Armenia. This study attempts to examine the creation of a political myth in the artistic space of Charents’ novel. The concept of "political myth" has become the subject of scientific definition and research after the Second World War, but the creation of a political myth in Charents’ novel precede the scientific observations of future theorists about this phenomenon. In the article, the relationship between the theoretical perceptions of the political myth and its artistic representation in the novel is revealed through an interdisciplinary analysis. The political myth becomes an object of study as a tool of influence on the masses in the novel. The artistic means by which this myth is created are examined. Reference is made to language as a means of political myth formation and influence. From the point of view of the studied problem, the modernity of the novel is emphasized due to the importance of political myth and speech in modern society.